Magnetic field compatible circuit quantum electrodynamics with graphene Josephson junctions. Issue 1 (December 2018) - Kroll, J.; Uilhoorn, W.; Enden, K.; Jong, D.; Watanabe, K.; Taniguchi, T.; Goswami, S.; Cassidy, M.; Kouwenhoven, L.
Abstract Circuit quantum electrodynamics has proven to be a powerful tool to probe mesoscopic effects in hybrid systems and is used in several quantum computing (QC) proposals that require a transmon qubit able to operate in strong magnetic fields. To address this we integrate monolayer graphene Josephson junctions into microwave frequency superconducting circuits to create graphene based transmons. Using dispersive microwave spectroscopy we resolve graphene's characteristic band dispersion and observe coherent electronic interference effects confirming the ballistic nature of our graphene Josephson junctions. We show that the monoatomic thickness of graphene renders the device insensitive to an applied magnetic field, allowing us to perform energy level spectroscopy of the circuit in a parallel magnetic field of 1 T, an order of magnitude higher than previous studies. These results establish graphene based superconducting circuits as a promising platform for QC and the study of mesoscopic quantum effects that appear in strong magnetic fields. A transmon qubit insensitive to magnetic fields is a crucial element in topological quantum computing. Here, Kroll et al. create graphene transmons by integrating monolayer graphene Josephson junctions into microwave frequency superconducting circuits, allowing them to operate in a parallel magnetic field of 1 T.